ANALISIS PENILAIAN KONSUMEN TERHADAP KESADARAN MEREK RESTORAN FAST FOOD DI JAKARTA - Megah Wijaya; Yenli Megawati (Universitas Bunda Mulia, 2017)
The purpose of this survey is to know the highest and the lowest brand awareness and brand association of fast food restaurant in Jakarta. In-depth interview and questionnaire are the method the research. There were 200 respondents purposively selected.Data analysis using mean and validity and realibility for questionnaire produce the following results: (1) Top of Mind – KFC (2) Brand Recall – McDonald’s (3) Brand Recognition – KFC (4) Brand Equity – KFC (5) Brand Preference – McDonald’s (6) Brand Uniqueness – McDonald’sKey Words:Brand, Brand Awareness, Brand Association, Fast Food Restaurant